Osteoporosis pathogenesis and treatment: existing and emerging avenues - Liang, Bo; Burley, George; Lin, Shu; Shi, Yan-Chuan (Cellular & molecular biology letters, 2022)
Osteoporotic fractures lead to increased disability and mortality in the elderly population. With the rapid increase in the aging population around the globe, more effective treatments for osteoporosis and osteoporotic fractures are urgently required. The underlying molecular mechanisms of osteoporosis are believed to be due to the increased activity of osteoclasts, decreased activity of osteoblasts, or both, which leads to an imbalance in the bone remodeling process with accelerated bone resorption and attenuated bone formation. Currently, the available clinical treatments for osteoporosis have mostly focused on factors influencing bone remodeling; however, they have their own limitations and side effects. Recently, cytokine immunotherapy, gene therapy, and stem cell therapy have become new approaches for the treatment of various diseases. This article reviews the latest research on bone remodeling mechanisms, as well as how this underpins current and potential novel treatments for osteoporosis.